Variações sobre o mesmo tonto: o herói cômico e a construção dramatúrgica do humor no cinema de Francis Veber - Leonardo Antunes Cunha (2011)
This research ventures into a field that is very popular among movie audiences but not as highly valued in cinema studies: film comedy. Its chosen corpus encloses films written and directed by an artist that is also scarcely studied, even among experts in the field of Cinema and even in his own country: Francis Veber, the French veteran who has written over 30 films and directed 12.The dual purpose of the research is to contribute to the discussion of cinema as entertainment, mainly in its dramaturgical aspect, and also to shed more light on the work of Veber, an artist who shows ability on dealing with the construction of humorous narratives and on blending various types of comicality, and one that often excels the canons of comedy. Therefore, the research intends to combine the study of so-called "genre cinema" (comedy, in this case) and "auteur cinema" (by seeking the stylistic traits of the filmmaker), valuing the dialogue between these two fields and not treating as divergent. To this end, it follows three conceptual axes: the characterization of the comic hero in its various manifestations; the narrative structures in film comedy; and the various forms of comicality (burlesque, situational, satirical, parodic and verbal), all the while linking these axes with Vebers films. Next the research studies two specific traits in Vebers oeuvre, notably in the so-called "Pignon Saga": his peculiar strategy of casting throughout the saga,and also the transformation of François Pignon from character to meta-character.These reflections may help in the study or development of screenplays that take comicality into account and that value the involvement of the spectator in the construction of film discourse.